Regulation of plasma triglyceride metabolism : some nutritional and endocrine effects - Chait, Alan (Not Specified, 2024)
During the past two and a half decades, numerous studies on plasma lipids and lipoproteins have appeared in the medical literature. The tremendous interest in this field, no doubt relates largely to the long-known and well established association between· elevation of plasma lipids and lipoproteins, and ischaemic heart disease (IHD). Despite many years of study iri this field, the nature of this association is still poorly understood. The exact mechanism whereby plasma lipids and lipoproteins influence the pathogenesis of atherosclerosis still remains to be elucidated.